Key factors influencing Generation Z participation in Islamic mutual funds in Indonesia - Majid, Haidar; Majid, Rifaldi (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study aims to examine the influence of promotion, Sharia financial literacy, and risk on the investment decision of Generation Z in Islamic mutual funds through their Bibit application.Methodology – Thei study employed a quantitative approach involving 172 Generation Z respondents. Primary data were collected using questionnaires, and the analysis was conducted using structural equation modeling with partial least squares (SEM-PLS) through SmartPLS 3.2.9 to evaluate the relationships between variables.Findings – The results indicate that promotion, Sharia financial literacy, and perceived risk have a positive and significant effect on investment intention in Islamic mutual funds. Among these variables, Sharia financial literacy showed the strongest influence, followed by perceived risk and promotion. The positive effect of perceived risk suggests that Generation Z investors who are more aware of potential risks tend to exhibit higher investment decisions, as risk awareness enhances preparedness, confidence, and informed decision-making rather than discouraging participation. Implications – The strong effect of Sharia financial literacy underscores the importance of educational programs and financial knowledge dissemination targeted at Geineiration Z. Financial service providers are encouraged to einhancei promotional strategies and maintain transparent risk commuinication to build trust and increiasei participation in Islamic mutual funds.Originality – This reiseiarch einricheis thei liteiratuirei on Islamic digital investment behavior among Generation Z by integrating behavioral aspeicts of financial liteiracy and peirceiiveid risk in thei conteixt of digital inveistmeint applications. Thei stuidy provideis neiw insights into how youing, teichnology orieinteid Muislim inveistors eingagei with Sharia-compliant investment platforms.